Cancel Culture di Twitter: Etnografi Virtual Kasus Gofar Hilman dan Radio Prambors di Akun @Prambors - Roseline Roseline; Julius Julius; Laura Christie Abigail Boseke; Setika Sidhik Nurhidayat (Cakrawala - Jurnal Humaniora, 2023)
The cancel culture phenomenon is an action that has become a culture in today's digital era, especially on social media platforms. The case of Gofar Hilman and Radio Prambors that went viral at that time made us as researchers want to take a deeper look at the virtual ethnography of the case, especially on Twitter. The purpose of this research is to get an idea about the effect of cancel culture on Twitter on people's responses in Indonesia. This study uses a constructivist paradigm using qualitative research methods and descriptive studies. To strengthen the validity of this study, data collection techniques were used through literature studies about new media and document analysis in the form of Tweets in the comments column uploaded by Radio Prambors’s account, @Prambors on Twitter. The results of this study indicates that the cancel culture in Indonesia often shows their cohesiveness by throwing comments in the form of negative sentiments, but in the end sometimes these actions produce something with action after a phenomenon has gone viral.